2004
DOI: 10.5993/ajhb.28.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Change in Diet, Physical Activity, and Body Weight in Female College Freshman

Abstract: To examine diet, physical activity, and bodyweight changes associated with relocation from home to university. Methods: Diet, fitness/physical activity, bodyweight parameters and self-efficacy were assessed among 54 freshman women upon college entry and 5 months later. Results: Although caloric intake significantly decreased, a significant increase occurred in bodyweight parameters that may be attributed to significant decreases in total physical activity. Conclusions: Interventions are needed aimed at increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
228
8
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(263 citation statements)
references
References 21 publications
(27 reference statements)
18
228
8
6
Order By: Relevance
“…The mean weight gain was reduced to 1.6 kg, but remained significantly different (Po0.01) from the experimental group. Levitsky et al 12 1.9 Anderson et al 13 1.3 Hovell et al 14 1.3 Butler et al 15 0.59 Matvienko et al 16 1.8…”
Section: Resultsmentioning
confidence: 99%
“…The mean weight gain was reduced to 1.6 kg, but remained significantly different (Po0.01) from the experimental group. Levitsky et al 12 1.9 Anderson et al 13 1.3 Hovell et al 14 1.3 Butler et al 15 0.59 Matvienko et al 16 1.8…”
Section: Resultsmentioning
confidence: 99%
“…Engaging in moderate and vigorous physical activity (PA) has been shown to be influenced by various life events, such as decreasing activity following marriage, declining health, the birth of the first child and transitioning from school to university or the workforce (Bell and Lee, 2006, Butler et al, 2004, Brown et al, 2009. It is conceivable that these life events may also influence ST.…”
Section: Introductionmentioning
confidence: 99%
“…Seven of those studies 26,27,29,36,37,40,41 suggested that diet quality was a predictor of weight gain, with inadequate consumption of fruit and vegetables 27,29,36,40,41 , low fibre 26 and high fat/cholesterol 26, 27, 37 diets being commonplace amongst the students. Of these seven studies, five measured diet/dietary changes using a dietary behaviour questionnaire 26,29,37,40,41 , while two measured diet using a food frequency questionnaire (FFQ) 27,36 . The use of the FFQ allowed one study to report changes in caloric intake 27 .…”
Section: Contraceptionmentioning
confidence: 99%
“…Of these seven studies, five measured diet/dietary changes using a dietary behaviour questionnaire 26,29,37,40,41 , while two measured diet using a food frequency questionnaire (FFQ) 27,36 . The use of the FFQ allowed one study to report changes in caloric intake 27 . In that study, while average caloric intake decreased by 349 kcal/day over the five month period, consumption of alcohol and percent fat intake increased, and fruit and vegetable intake decreased 27 .…”
Section: Contraceptionmentioning
confidence: 99%
See 1 more Smart Citation